Comparative Study Of Intravenous Paracetamol And Dexmedetomidine On Perioperative Hemodynamics And Postoperative Pain Relief For Laparoscopic Cholecystectomy (Journal of Pharmaceutical Negative Results, 2023)
Background: Unrelieved post-operative pain may bring about physical suffering as well as a couple of physiological and mental effects, which may adversely affect the peri-operative outcome and make contributions to growth during the period of stay in the health center. Aim and objective: The study aimed to assess the comparative evaluation of dexmedetomidine and paracetamol on preoperative and postoperative hemodynamics and analgesia for patients undergoing laparoscopic cholecystectomy. Material and methods: 50 consenting, American society of Anesthesiologist-physical status-I (ASA-ps-I), female patients, aged 20-60 yr become randomly assigned to one of the following groups: group P (n = 25) received IV 1g Paracetamol infusion over 10 min pre-operatively and 6 hourly thereafter and group D (n = 25) received IV Dexmedetomidine 1 μg/kg bolus over 10 min pre-operatively and 0.2-0.4 μg/kg/hr thereafter for 24 hrs. Preoperative hemodynamic variables, postoperative pain scores, and the needs for rescue analgesics have been recorded andcompared. Results: Profiles of intra-operative hemodynamic changes had been similar in each group regarding heart rate (HR), diastolic blood pressure (DBP), and mean arterial pressure (MAP) except within the systolic blood pressure (SBP) where Dexmedetomidine significantly decreased it compared to Paracetamol (P = 0.014). Postoperatively 4th hrs and 24th hrs changes in mean HR between the two groups changed into a statistically significant (P < 0.05). Visual analog scale scores have been significantly lower inside group P than in group D at 8th, 16th, and 24th hrs (P < 0.001). Sedation scores have been statistically better inside group D compared with group P at postoperative 4th, 8th, 16th, and 24th hrs (P < 0.006). Conclusion: Paracetamol is superior to Dexmedetomidine for analgesia in short surgical procedures and should form a part of multi-modal analgesia. The use of paracetamol provides multimodal analgesia with minimum sedation in short surgical procedures and dexmetetomidine provides analgesia and cooperative sedation